THE VALIDITY PRESUPPOSITIONS FOR THE PUBLIC INTEREST PROROGATION OF PUBLIC SERVICE CONCESSIONS (Revista Direito em Debate, 2020)
This article deals with the prorogation of public service concessions for mere reasons of convenience and opportunity of the parties (or public interest prorogation). Its purpose is to verify the validity presuppositions of this species of prorogation – considered by the federal Executive Branch as one of the main instruments to encourage new private investments in key infrastructure sectors for the development of Brazil. The method of approach of the theme is the deductive, and the research method, the bibliographic. Finally, the main conclusion of this article is that the validity presuppositions of the public interest prorogation are: (i) provision in law; (ii) grant preceded by public bidding; (iii) provision in the bid notice; (iv) concession in force; (v) non realization of public interest prorogation previously; (vi) faithful fulfillment of the contract by the concessionaire; (vii) advantage of the measure; (viii) agreement between the parties; and (ix) qualification in the Investment Partnership Program – PPI.
Keywords: Administrative law; public service; concession; prorogation; validity presuppositions